Hopes and fears: emerging adults in mood and anxiety disorder treatment predict outcomes of the COVID-19 pandemic. Issue 3 (4th May 2022) - Wammes, Michael; Summerhurst, Carolyn; Demy, Jazzmin; Vingilis, Evelyn; Tremblay, Paul F.; Carter, Chlöe; Osuch, Elizabeth
ABSTRACT: Active patients at The First Episode Mood and Anxiety Program (FEMAP) were asked to participate in a study monitoring their symptoms during early COVID-19 closures. Participants were asked to predict both possible positive and feared outcomes of the pandemic. Responses were analyzed with a descriptive qualitative approach using thematic analysis. Primary feared outcomes included death, prolonged pandemic impacts, and concerns about employment, mental health, and education. Prevalent positive predictions included a new perspective, improved relationships, personal growth, and environmental improvement. These findings suggest the complex relationship between fear and hope for young people in the early stages of the pandemic.